(untitled) - Buckley, William F. (Hoboken, N.J., 2004)
The fall of the Berlin Wall in November 1989 was the turning point in the struggle against Communism in Eastern Europe. The culmination of popular uprisings in Hungary, Poland, and East Germany, the Wall's fall led inexorably to revolutions in Czechoslovakia and Romania, the reunification of Germany, and, ultimately, the disintegration of the Soviet Union itself. In this book, American conservative pioneer and National Review founder William F. Buckley Jr. explains how and why the Cold War ended as it did-and what lessons we can draw from the experience. Writing with his legendary wit and insight, he brings to life Communism's last gasp, showing how Reagan's hard-nosed foreign policy and Gorbachev's reforms undermined Warsaw Pact dictators, emboldened dissidents, and finally made the dream of freedom a reality in Eastern Europe. * Written by one of America's most erudite and influential political thinkers and writer. * Includes a new foreword by Henry Kissinger marking the 20th anniversary of the opening of the Berlin Wall * Hailed as "eloquent [and] immensely readable" (Baltimore Sun), this account "celebrates the tenacity of the human spirit and the will to achieve freedom" (Publishers Weekly). Sure to delight conservatives, annoy liberals, and enlighten everyone who reads it, The Fall of the Berlin Wall is William F. Buckley Jr. at his inimitable best.
Keywords: Berlin Wall, Berlin, Germany, 1961-1989.,Cold War,Bức tường Berlin Đức 1961-1989,Chiến tranh lạnh